2020
DOI: 10.3390/app10082975
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Biogas Production from Processing Residues to Reduce Environmental Impacts from Cassava Starch and Crisp Production—A Case Study from Malaysia

Abstract: The cultivation of cassava (Manihot esculenta) is widely spread in a variety of tropical countries with an estimated annual production of 291.9 million tons. The crop is the most important source of carbohydrates in producing countries. In Malaysia, cassava is mainly cultivated for starch production. Despite the economic and nutritional importance of cassava, there is only limited knowledge available regarding the overall environmental impacts of cassava starch production or the production of alternative food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
2
17
0
4
Order By: Relevance
“…The production of rice flour and plastic for LS production were found to emit 43.322 kg 1, 4-DCB and 4.125 kg 1, 4-DCB respectively. The latter findings from FC production are in line with the ecotoxicity impacts of a similar product of crisps described by Lansche et al [30]. In this study, it was found that the least significant contributors for METP was TP production at 9.166 kg 1, 4-DCB of which soybean production accounted for 4.67 kg 1, 4-DCB.…”
Section: Marine Ecotocixity (Metp)supporting
confidence: 91%
See 1 more Smart Citation
“…The production of rice flour and plastic for LS production were found to emit 43.322 kg 1, 4-DCB and 4.125 kg 1, 4-DCB respectively. The latter findings from FC production are in line with the ecotoxicity impacts of a similar product of crisps described by Lansche et al [30]. In this study, it was found that the least significant contributors for METP was TP production at 9.166 kg 1, 4-DCB of which soybean production accounted for 4.67 kg 1, 4-DCB.…”
Section: Marine Ecotocixity (Metp)supporting
confidence: 91%
“…The production of rice flour and plastic for LS production were found to emit 43.322 kg 1, 4-DCB and 4.125 kg 1, 4-DCB respectively. The latter findings from FC production are in line with the ecotoxicity impacts of a similar product of crisps described by Lansche et al [30].…”
Section: Marine Ecotocixity (Metp)supporting
confidence: 91%
“…For water, soil, and air resources, the benefits refer to the reduction of about 90% in the demand for firewood, a reduction of 34 thousand tons CO 2 equivalent due to the capture of methane gas generated in the first effluent treatment pond, as presented by Guimarães et al (2014). Lansche et al (2020) used the life cycle assessment (LCA) tool to compare different scenarios of cassava production and processing and concluded that environmental impacts can be reduced if the biogas resulting from the use of waste is used for production of electricity and heat. Igliński et al (2020) also point out that one of the basic advantages of agricultural biogas is its versatility, in comparison with other renewable energy sources, to generate electricity and heat.…”
Section: Results and Analysismentioning
confidence: 99%
“…Wasteswater from cassava starch processing contains waste starch, fibers, minerals, and cyanogenic compounds. This waste stream, despite being diluted in water, presents a significant concentration of organic matter and requires to be treated before being discharged into the nearby watercourses (Lansche et al, 2020;Sánchez et al, 2017). The starch industry is the second most energy-consumed industry subsector that consumes almost 6.2% of the food, beverage, and tobacco industrial sector (Assawamartbunlue and Luknongbu, 2020).…”
Section: Introductionmentioning
confidence: 99%